Development of “bisnaguinha” bread fibre source - Coutinho , Juliane dos Santos; Silva, Iris Laura Lima da; Goes , Elenice Souza dos Reis; Tobal , Thaise Mariá (Food Science and Technology, 2023)
Fibre-source “bisnaguinha” breads were developed using the addition of sweet passion fruit peel flour. The developed formulations were evaluated for physical properties, chemical composition and sensory acceptability. The flour obtained was characterised in terms of dietary fibre content and used as a partial substitute for wheat flour, in the proportions of 11.5%, 17.3% and 23%. The flour of sweet passion fruit peel presented high content of dietary fibre and its addition in the formulations of breads resulted in an increase in the content of ash, lipids and fibres, and all “bisnaguinha” breads with added fruit peel flour were considered a source of fibres. The addition of peel flour did not affect the hardness, chewability and shear force of the bread. Regarding sensory acceptability, all samples had good acceptance, and the proportion of 11.5% was closer to the standard bread, which obtained the highest scores. It is concluded, therefore, that it is feasible to use this flour in the preparation of breads, adding nutritional value to the products, and with good physical and sensorial characteristics. Practical application: Use of flour from sweet passion fruit peel in the production of fibre source breads.